A network integrative approach to unravel new links between NMD and mRNA processing pathways - Nogueira, Gonçalo (2017)
Nonsense-mediated mRNA decay (NMD) is a surveillance pathway that recognizes and selectively degrades mRNAs carrying premature translation termination codons (PTCs). This process has been associated with many genetic diseases and some forms of cancer caused by nonsense or frameshift mutations that introduce PTCs. Moreover, recent studies have shown that NMD is also involved in the regulation of a large number of transcripts, suggesting a major role in the control of gene expression. To further investigate the biological relevance of NMD and how this process can be modulated, we used a network analysis approach that integrates 1) protein-protein, 2) kinasetarget, 3) phosphatase-target, 4) miRNA-target, 5) transcription factors-target, 6) gene co-expression, 7) ubiquitination and 8) signaling interactions. The generated network was used to find novel NMD-associated proteins, prioritizing candidates with simultaneous interactions with different mRNA processing pathways (mRNA splicing, mRNA transport, mRNA translation and mRNA decay). Taking in account all information sources integrated in our network, we have created a scoring algorithm to identify new potentially important players in NMD, which can be essential to further understand the interplay between mRNA translation, PTC definition and NMD. Due to the diversity of regulatory links integrated in this workflow, we propose it can be applied to find molecular bridges between related biological processes and generate novel hypotheses about the molecular mechanisms co-regulating these phenomena.